Consistency of teachers and parents in the formation of polite character in early childhood - Utami, Wahyu Tri; Azizah, Nurul (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2025)
Background: The formation of polite and respectful character in early childhood requires continuous support from both schools and families. In practice, some children still do not demonstrate respectful attitudes toward teachers and peers, indicating a lack of consistency between habituation practices at school and their application at home. Objective: This study aims to describe the consistency of teachers and parents in shaping children’s polite character at RA Roudlotul Ulum Baluk. Specifically, the study analyzes the alignment of character-building practices related to politeness between teachers and parents within the context of a village-based Islamic early childhood education institution. Method: This research employed a descriptive qualitative approach involving seven informants, consisting of the head of the RA, one teacher from Class A, one teacher from Class B, and four parents of students at RA Roudlotul Ulum Baluk. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using the stages of data reduction, data display, and conclusion drawing. Results: The findings indicate that: 1) Teachers consistently implement politeness habituation through greetings, queuing practices, and the use of polite language at school. 2) Some parents apply similar practices at home; however, these practices are not carried out consistently. 3) Inconsistencies in habituation at home make it difficult for some children to maintain polite behavior when they are at school. Conclusion: The development of polite character at RA Roudlotul Ulum Baluk can be achieved effectively through the alignment of habituation practices between school and family. Consistent practices implemented by teachers and reinforced by parents play a crucial role in the learning process, enabling children to sustain polite behavior continuously from an early age.